A Large Anisotropic Enhancement of the Charge Carrier Mobility of Flexible Organic Transistors with Strain: A Hall Effect and Raman Study. Issue 1 (13th November 2019) - Choi, Hyun Ho; Yi, Hee Taek; Tsurumi, Junto; Kim, Jae Joon; Briseno, Alejandro L.; Watanabe, Shun; Takeya, Jun; Cho, Kilwon; Podzorov, Vitaly
Abstract: Utilizing the intrinsic mobility–strain relationship in semiconductors is critical for enabling strain engineering applications in high‐performance flexible electronics. Here, measurements of Hall effect and Raman spectra of an organic semiconductor as a function of uniaxial mechanical strain are reported. This study reveals a very strong, anisotropic, and reversible modulation of the intrinsic (trap‐free) charge carrier mobility of single‐crystal rubrene transistors with strain, showing that the effective mobility of organic circuits can be enhanced by up to 100% with only 1% of compressive strain. Consistently, Raman spectroscopy reveals a systematic shift of the low‐frequency Raman modes of rubrene to higher (lower) frequencies with compressive (tensile) strain, which is indicative of a reduction (enhancement) of thermal molecular disorder in the crystal with strain. This study lays the foundation of the strain engineering in organic electronics and advances the knowledge of the relationship between the carrier mobility, low‐frequency vibrational modes, strain, and molecular disorder in organic semiconductors. Abstract : This paper reports Hall effect and Raman measurements of organic semiconductors as a function of uniaxial mechanical strain. It reveals a strong, anisotropic modulation of the intrinsic charge carrier mobility of single‐crystal rubrene transistors with strain, showing that the performance of organic circuits can be enhanced by up to 100% with only 1% of compessive strain.